Programma: 7-10 november Hard hearted Hannah; 14-17 november Figurentheater Triangel; 21-24 november Impuls Theater; 28 november - 1 december The First Church of the Phantom Captain (Reformed) - Flaum, Mick,
Programma: 7-10 november Hard hearted Hannah; 14-17 november Figurentheater Triangel; 21-24 november Impuls Theater; 28 november - 1 december The First Church of the Phantom Captain (Reformed).